Cover Image, Volume 38, Issue 6. (24th May 2018) - Lin, Shaobin; Shi, Shanshan; Zhou, Yi; Ji, Yuanjun; Huang, Peizhi; Wu, Jianzhu; Chen, Baojiang; Luo, Yanmin
Abstract : Single nucleotide polymorphism array and TBX6 sequencing results in a fetus with a recurrent 16p11.2 microdeletion. Figure modified from Lin et al., in this issue. https://doi.org/10.1002/pd.5245 .